Short‐Time Compensation as a Tool to Mitigate Job Loss? Evidence on the U.S. Experience During the Recent Recession1. Issue 4 (October 2014) - Abraham, Katharine G.; Houseman, Susan N.
<x xml:space="preserve">Abstract</x> During the recent recession only seventeen states offered short‐time compensation (STC)—prorated unemployment benefits for workers whose hours are reduced for economic reasons. Federal legislation passed in 2012 will encourage the expansion of STC. Exploiting cross‐state variation in STC, we present new evidence indicating that jobs saved during the recession as a consequence of STC may have been significant in manufacturing, but that the overall scale of the STC program was generally too small to have substantially mitigated aggregate job losses in the seventeen states. Expansion of the program is necessary for STC to be an effective countercyclical tool in the future.